Estado del arte sobre estaciones terrenas para pequeños satélites - Ferreira, Mauricio Gonçalves Vieira; dos Santos, Walter Abrahão; Espíndola Diaz, Jorge Enrique (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2020)
In order to deepen the knowledge on ground stations for pico-satellite and nano-satellite control, it is necessary to know the state of the art of automation, the evolution and the latest developments in this technology. Also, it is necessary to know: used communication protocols; CubeSat projects that were developed or are currently being developed; organizations that regulate the use of pico-satellites; the design of ground stations; the most used software for tracking satellites, and to look into known techniques for satellite tracking. This work is a compilation of the papers published concerning the evolution of ground system in the last 10 years. In addition, it provides a summary and critical analysis on state of the art to ground station. The objective of this work is to make a state of the art in ground station for miniaturized satellites, to evaluate the existence of the use of artificial intelligence techniques in the automation of ground stations and identify how institutions are working on ground station around the world.